2021
DOI: 10.1186/s12870-021-02930-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of virulence associated milRNAs and their bidirectional targets in Rhizoctonia solani and maize during infection

Abstract: Background Anastomosis group 1 IA (AG1-IA) of Rhizoctonia solani is the major agent of banded leaf and sheath blight (BLSB) disease that causes severe yield loss in many worldwide crops. MicroRNAs (miRNAs) are ~ 22 nt non-coding RNAs that negatively regulate gene expression levels by mRNA degradation or translation inhibition. A better understanding of miRNA function during AG1-IA infection can expedite to elucidate the molecular mechanisms of fungi-host interactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…Interestingly, R. solani milRNAs showed their targets in the host (rice) genome also. A similar observation was made on R. solani targeting maize genes [ 25 ]. Recently, cross kingdom regulation of genes by miRNAs during host–pathogen interaction has been demonstrated in several pathosystems [ 41 ].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Interestingly, R. solani milRNAs showed their targets in the host (rice) genome also. A similar observation was made on R. solani targeting maize genes [ 25 ]. Recently, cross kingdom regulation of genes by miRNAs during host–pathogen interaction has been demonstrated in several pathosystems [ 41 ].…”
Section: Discussionsupporting
confidence: 78%
“…The novel milRNA scaffold13_22000 showed >6000 read count which emphasizes that several novel players identified in this study might regulate fungal genome. Earlier studies suggested that such novel milRNAs may have crucial roles in pathogenesis and virulence of R. solani [ 21 , 25 ]. 1725 target genes of 128 known and 22 novel milRNAs were identified that are involved in various metabolic and developmental processes of fungi indicating that milRNAs are major regulators of the R. solani genome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations